Alternative explanation of North Korea's survival: successful application of smart power - Shin, D. W. (Cranfield University, 2017)
The original contribution of this study is to demonstrate how North Korea survives by using smart power. The existing literature has offered partial explanations, but many have lost their explanatory power over time and there seems to be no definitive answer to explain how North Korea survives. This multi-case study was designed to explore how the North uses smart power by examining its provocations from the Korean War to August 2015. The rationale for this study is to increase understanding of Pyongyang’s behavior and offer recommendations to bring long-term stability to the Korean Peninsula. This study purposefully began with the Korean War because it was assumed that, without understanding the origin of North Korean provocations, it would be difficult to provide the proper temporal context for other provocations. This study reveals that Kim Il-sung and his guerrillas consolidated power and established totalitarian rule dominated by his Juche ideology (self-reliance). Subsequently, they waged a long war of reunification from 1948 to the 1980s. Although Kim’s smart power attempts failed to achieve his principal aim of reunification, when Beijing and Moscow abandoned him in the early 1990s he focused on regime survival. He bolstered his weak hand by playing the nuclear card to buy more time to ensure the hereditary succession by his son Kim Jong-il, who defied predictions he would not survive and proclaimed Songun (military-first) to deal with the changing international environment. He demonstrated his own skill by exploiting Seoul’s Sunshine Policy and successfully negotiating three nuclear agreements with the U.S. After his death, Kim Jong-un waged a reign of terror to consolidate power and manufactured crises to bolster his legitimacy and demonstrate his leadership. He also invoked his grandfather’s anti-Japanese legacy and the Byungjin policy (simultaneous development of nuclear weapons and the economy) to legitimize his rule. The evidence shows he is rational and that offers opportunities to resolve the North Korea issue.